Investigation of the relationship between attention skills and science process skills in children regarding external elements - GÜVEN, GÜLÇİN (Ankara University, 2020)
In this research, it is aimed to examine the relationship between the attention skills of children regarding auditory and visual elements and their science process skills. In addition, these skills were examined in terms of gender and socio-economic level variables. The research is designed in survey model and the study group is consisted of randomly selected 156 children aged 60-72 months attending preschool education institutions in the 2018-2019 academic year in Istanbul. Four data collection tools as Demographic Information Form, Preschool Science Process Skills Scale for 60-72 Months Old Children, Listening Test and Concentration Test for 5-Year-Old Children were used in the research. As the result of the research, it is found a positive significant relationship between the visual and auditory attention skills of the preschool children and science process skills. It was found that the science process skills and auditory attention skills of preschool children did not differ significantly with gender. However, visual attention skills differed with gender of the children and this difference was in favor of the girls. Additionally, attention skills and scientific process skills differed with socio-economic level of the children and this difference was in favor of the upper socio-economic level. © 2020, Ankara University. All rights reserved.
Keywords: Attention skill; Preschool; Science process skill